2006
DOI: 10.1038/sj.onc.1210130
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 E6 confers p53-dependent and p53-independent phenotypes in the epidermis of mice deficient for E6AP

Abstract: High-risk human papillomaviruses are the causative agents of cervical and other anogenital cancers. In these cancers, two viral oncogenes, E6 and E7, are expressed. E6 is best known for its ability to inactivate the tumor suppressor p53, which is thought to arise through ubiquitin-mediated degradation of p53 and involve a ternary complex between E6, p53 and the E3 ligase, E6AP. In mice transgenic for wild-type HPV16 E6, its expression leads to epithelial hyperplasia and an abrogation of normal cellular respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…Our data demonstrate that E6AP is not required for hTERT activation and therefore suggest that NFX1-91 destabilization is not necessary or that another E6-dependent pathway may specifically target NFX1-91. This is consistent with recent observations that E6-induced p53 degradation in vivo may occur through E6AP-dependent and E6AP-independent mechanisms (6,7,40).…”
Section: Resultssupporting
confidence: 81%
“…Our data demonstrate that E6AP is not required for hTERT activation and therefore suggest that NFX1-91 destabilization is not necessary or that another E6-dependent pathway may specifically target NFX1-91. This is consistent with recent observations that E6-induced p53 degradation in vivo may occur through E6AP-dependent and E6AP-independent mechanisms (6,7,40).…”
Section: Resultssupporting
confidence: 81%
“…While E6AP is required for in vitro degradation systems (9) and immortalized mouse fibroblasts (5), E6AP-null mice that express 16E6 in the skin do not accumulate p53 when irradiated, and mouse embryo kidney cells from those E6AP-null mice are reported to lose p53 upon overexpression of 16E6 (12,22). Further, ubiquitin-independent degradation of p53 by E6 has been described (2).…”
mentioning
confidence: 99%
“…Therefore any radiation damage would not be sufficiently repaired, and damaged cells would be more likely to die during mitosis as they progress through the cell cycle. E6 has previously been shown to sensitize mammary epithelial cells, fibroblasts and keratinocytes to chemically induced death (Xu, Meikrantz et al 1995, Hawkins, Demers et al 1996, Liu, McKalip et al 2000, Liu, Zhao et al 2007), but has been reported to have the opposite effect or no effect in other cell types exposed to ionizing radiation or DNA-damaging chemicals (DeWeese, Walsh et al 1997, Hampson, El Hady et al 2001, Shai, Nguyen et al 2007). Thus, the radiosensitizing effect might be specific to a few cell types, including keratinocytes, the natural hosts for HPVs, and be dependent on the E6*I isoform.…”
Section: Discussionmentioning
confidence: 99%